Implementation of Religious Habits in Forming the Religious Character of Elementary Madrasah Students - Sri Rezeki; Yoga Prima Putra; Rahman Wahid (CV. Ksatria Siliwangi, 2026)
Islamic education is not only oriented towards developing cognitive aspects, but also emphasizes the formation of religious character of students from an early age, especially at the Madrasah Ibtidaiyah (MI) level. This study aims to analyze the application of religious habituation in shaping the religious character of students at Madrasah Ibtidaiyah Jauharul Huda. This study uses a qualitative approach with data collection techniques in the form of observation, interviews, and documentation. Research informants consisted of the madrasah principal and class teachers. The results of the study indicate that religious habituation at MI Jauharul Huda is carried out routinely and scheduled through various activities such as, dhuha prayer, dzuhur prayer in congregation, reading and writing the Qur'an (BTQ), memorization, prayers before and after learning, and the implementation of the 5S culture (greeting, smiling, greeting, politeness and courtesy). These habits have a positive impact on the formation of students' religious character, which is reflected in attitudes of discipline, honesty, and responsibility. The success of the program is supported by the role of the principal, teachers, and parents. The obstacles faced include limited student equipment, lack of parental attention, and less than conducive classroom conditions. This research is expected to provide evaluation material and recommendations for madrasas in optimizing student character development.